Donor Assistance for Investment Climate Reforms and for Direct Support to Firms: An Overview of Available Data - Migliorisi, Stefano (Washington, DC: World Bank, 2012)
An investment climate consists of the location specific factors that shape opportunities and incentives for firms to invest productively, create jobs and expand their businesses. Government policies related to security of property, regulation, taxation, infrastructure, finance, labor and governance play a critical role in the investment climate by affecting the costs, risks and barriers to competition faced by firms. Bilateral donors and multilateral agencies have helped many developing countries with investment climate reforms through policy-based support, technical assistance and development assistance to fund investment in infrastructure. This paper presents data on support provided between 1998 and 2002 for investment climate reforms.